Ab-initio study of optoelectronic and magnetic properties of the orthorhombic NdMnO3 perovskite. (April 2015) - Bouadjemi, B.; Bentata, S.; Abbad, A.; Benstaali, W.
Abstract: Using the full potential linear augmented plane wave (FPLAPW) method based on density functional theory (DFT), we have studied the structural, electronic, optical and magnetic properties of the orthorhombic perovskite oxide NdMnO3, with both generalized gradient approximation (GGA) and GGA+ U approaches, where U is on-site Coulomb interaction correction. We have analyzed the structural parameters, total and partial densities of states. The results show a half-metallic ferromagnetic ground state for NdMnO3 in GGA+ U due to the strong hybridization effect between Mn 3d and Nd 4 f states The integer value of the total magnetic moment is one of the significance of the half metallic nature of this material. Furthermore, we have computed optical properties of NdMnO3 ; we found pronounced peaks occurring in different parts of the spectrum. The results obtained, make the orthorhombic NdMnO3 a promising candidate for application in spintronics and opto-electronics. Highlights: PrMnO3 is semi-metallic for GGA. PrMnO3 is half-metallic for GGA+U. PrMnO3 is ferromagnetic. Bond character is partial ionic and partial covalent.